Lembaga Pendidikan Islam dalam Menghadapi Derasnya Perubahan - Erwin Indrioko (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2016)
This article discusses how Islamic educational institutions can exist in the era of fast-paced change. No doubt the challenge of Islamic education is very complex, one of which is a change. The main factor in the change is the advancement of information and communication technology, competition amonginstitutions, and the demands of society. In facing changes very vital leadership role, he should be able to influence and mobilize all the components to continue to work in facing the swift currents of change. Unity of direction and the interconnections between components (educators, employees, and students) in Islamic educational institutions should be maintained, so that all the elements in the institution become solid and strong. In addition, the leaders should also keep the consistency of a system that exists in Islamic educational institutions. A strong system will generate a strong culture that characterizes Islamic educational institutions in the implementation process of education.